Seemed like a good idea : alchemy versus evidence-based approaches to healthcare management innovation - Pauly, Mark V., 1941- (Cambridge : Cambridge University Press, 2022)
Consumers, public officials, and even managers of health care and insurance are unhappy about care quality, access, and costs. This book shows that is because efforts to do something about these problems often rely on hope or conjecture, not rigorous evidence of effectiveness. In this book, experts in the field separate the speculative from the proven with regard to how care is rendered, how patients can be in control, how providers should be paid, and how disparities can be reduced - and they also identify the issues for which evidence is currently missing. It provides an antidote to frustration and a clear-eyed guide for forward progress, helping health care and insurance innovators make better decisions on deciding whether to go ahead now based on current evidence, to seek and wait for additional evidence, or to move on to different ideas. It will be useful to practitioners in hospital systems, medical groups, and insurance organizations and can also be used in executive and MBA teaching.
Title from publisher's bibliographic system (viewed on 18 Jul 2022).
Keywords: Evidence-based medicine; Health services administration